1998
DOI: 10.1016/s0016-5085(98)70027-7
|View full text |Cite
|
Sign up to set email alerts
|

Regenerating gene protein may mediate gastric mucosal proliferation induced by hypergastrinemia in rats

Abstract: Gastrin stimulates the production of Reg protein in gastric ECL cells, which may be involved in the gastrin-induced gastric mucosal cell growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
148
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 168 publications
(155 citation statements)
references
References 30 publications
6
148
0
1
Order By: Relevance
“…*p Ͻ 0.05 compared with both the control and single-dose groups. for RegI in cellular proliferation is well demonstrated in pancreas (Francis et al, 1992;Miyaura et al, 1991;Watanabe et al, 1994), and RegI has also been implicated as exerting trophic effects on the gastric epithelium (Asahara et al, 1996;Fukui et al, 1998;Higham et al, 1999;Kawanami et al, 1997;Kazumori et al, 2000). Moreover, our results show clear evidence of concordantly increased expression of RegI and PCNA in both damaged and healing gastric epithelium.…”
Section: Alderman Et Alsupporting
confidence: 74%
“…*p Ͻ 0.05 compared with both the control and single-dose groups. for RegI in cellular proliferation is well demonstrated in pancreas (Francis et al, 1992;Miyaura et al, 1991;Watanabe et al, 1994), and RegI has also been implicated as exerting trophic effects on the gastric epithelium (Asahara et al, 1996;Fukui et al, 1998;Higham et al, 1999;Kawanami et al, 1997;Kazumori et al, 2000). Moreover, our results show clear evidence of concordantly increased expression of RegI and PCNA in both damaged and healing gastric epithelium.…”
Section: Alderman Et Alsupporting
confidence: 74%
“…In addition to the role of Reg I in the pancreas, we have demonstrated that Reg I functions as a growth factor in gastric cells and is involved in gastric mucosal regeneration (Asahara et al, 1996;Fukui et al, 1998;Kazumori et al, 2000). Recently, we generated Reg I-transgenic mice, which showed that Reg I is a key regulatory molecule for the maintenance of the growth axis of the gastric glands (Miyaoka et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…1 Thereafter, its human homologue REG Ia protein was suggested to be involved in the pathophysiology of gastrointestinal inflammation and its associated cancer. [2][3][4][5][6] Indeed, we previously reported that REG Ia protein behaves as a trophic and/or an anti-apoptotic factor in the development of colitis-or gastritis-associated cancer. 5,6 To clarify the regulatory mechanism of REG Ia gene expression, we initially screened major cytokines and showed that interleukin (IL)-6 and IFN-g are possible stimulators of REG Ia gene expression under inflammatory conditions.…”
mentioning
confidence: 99%